Evaluation of Procalcitonin and Interleukin-6 as a Marker of Bacterial Urinary Tract Infection - Darogha, Suhaila N.; Azeez, Sarhang H.; Abdullah, Zhian G. (Cellular and Molecular Biology, 2022)
Urinary tract infection (UTI) is a major clinical problem in a wide age range that is associated with a high morbidity rate. Due to issues such as low specificity and the inability to differentiate between different types of infection in current diagnostic methods, there is a need to introduce novel UTI markers. The present study was conducted to evaluate the utility of Procalcitonin (PCT) and interleukin-6 (IL-6) as a marker of bacterial urinary tract infection. For this purpose, a cross-sectional study was conducted between November 2020 and February 2021 among 125 patients and 60 healthy volunteers (control) in Erbil Teaching Hospital. The concentration of PCT and IL-6 was quantified using the ELISA cloud immunoassay test. Between-group comparisons were assessed for the variables with analysis of variance. The results revealed that there was a significant difference between PCT levels in UTI patients (104.6±6.07) and control groups (54±2.24) (p <0.0001). The differences in IL-6 concentration in UTI patients (55.74±4.2) and control groups (24.56±2.4) were also significant (p <0.0001), implying that the level of both PCT and IL-6 increased due to bacterial infection in the urinary tract. As a whole, the findings of this study provide